Eosinophilic esophagitis: Current concepts of pathophysiology, diagnosis, and treatment - D. García-Compeán; A.R. Jiménez-Rodríguez; C.E. González-Martínez (Revista de Gastroenterología de México (English Edition))
Eosinophilic esophagitis (EoE) is a chronic, immune-mediated disease characterized by the infiltration of eosinophils into the esophageal mucosa. It is the most frequent cause of dysphagia and food impaction in adults. Due to its similar pathophysiology to allergic rhinitis, asthma, and atopic dermatitis, it has been considered the esophageal manifestation of allergy. It is more frequently seen in the United States, Europe, and Australia. Incidence and prevalence have increased significantly in those countries over the past three decades, to such a degree that some consider it an epidemic. The disease is infrequently diagnosed in Mexico and Latin America, and so little information on this disease is produced in our region of the world. The precise factors explaining this low incidence are unknown.On the other hand, there has been intense research on EoE in other parts of the world in recent years. Its pathophysiology has been better understood and endoscopic and clinical procedures have been refined for making the diagnosis. In addition, new drugs and special formulations of existing ones have been introduced for treating the disease. Simpler and more effective dietary treatment strategies have also been evaluated.The aim of the present work was to review the current status of EoE globally and in Mexico, emphasizing the probable factors (environmental and technical) that intervene in the low incidence recorded in our country. In addition, we conducted a review of the advances in research on the different aspects of EoE carried out in recent years. Resumen: La esofagitis eosinofílica (EEo) es una enfermedad crónica, inmunomediada caracterizada por infiltración de eosinófilos en la mucosa esofágica. Es la causa más frecuente de disfagia e impactación alimentaria en adultos. Por su fisiopatología similar a la rinitis alérgica, asma y dermatitis atópica se le ha considerado como la manifestación esofágica de la alergia. Se observa con mayor frecuencia en Estados Unidos, Europa y Australia. En estos países la incidencia y prevalencia se han incrementado significativamente en las últimas 3 décadas al grado que algunos la consideran una epidemia. En México y Latinoamérica es una enfermedad poco diagnosticada por lo que existe escasa información generada en nuestro país relacionada con esta patología. Se desconoce con precisión cuales son los factores que pudieran explicar esta baja incidencia.Por otra parte, globalmente ha habido una intensa investigación sobre la EEo en los últimos años, su fisiopatología ha sido mejor comprendida y se han afinado los procedimientos clínicos y endoscópicos para el diagnóstico. Además, se han introducido nuevos fármacos y formulaciones especiales de los ya existentes para el tratamiento, también se han evaluado estrategias más efectivas y simplificadas en el tratamiento dietético de estos pacientes.El objetivo del presente trabajo es revisar el estado actual de la EEo en el mundo y en México poniendo énfasis en los probables factores que intervienen en la baja incidencia registrada (medioambientales y técnicos) en nuestro país y, por otra parte, revisar los avances realizados en los últimos años de investigación sobre los diversos aspectos de la EEo.